Peningkatan Hasil Belajar IPA Materi Komponen Ekosistem melalui Media Puzzle Siswa Kelas V SD Negeri 01 Gunuang Malintang Kecamatan Pangkalan Koto Baru - PONI ERNIS; Nahdatul Hazmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study is to describe the improvement of student learning outcomes in science learning material for class V Ecosystem Components at SD Negeri 01 Gununag Malintang, Pangkalan District through Puzzle media for semester 1 of the 2019/2020 school year. This type of research is classroom action research, the subject of this research is the fifth grade students of SD Negeri 01 Gunuang Malintang. The research subjects were the fifth grade students of SD Negeri 01 Gunuang Malintang, totaling 28 students consisting of 9 male students and 19 female students. Data collection techniques in this study are observation and tests. Student learning outcomes in the pre-cycle is 68.92, the first cycle is 77.14 in the second cycle rose to 83.92. So it can be concluded that increasing student learning outcomes through puzzle media can improve student learning outcomes. From the results of the study it can be concluded that increasing student learning outcomes through puzzle media can improve student learning outcomes. Keywords: Learning Outcomes, Media Puzzle, Ecosystem Components